Extremely asymmetric ectasia: Tomographically unilateral keratoconus - Shabani, Hasan; Ramdas, Wishal D.; Meester‐Smoor, Magda A.; Rizopoulos, Dimitris; Klaver, Caroline C. W.; Dooren, Bart T. H.; Geerards, Annette J. M. (Acta ophthalmologica (Oxford, England), 2025)
Purpose To investigate the characteristics of apparently stable forms of tomographically unilateral keratoconus (KC). Methods In this retrospective case–control study, strict unilaterality criteria were applied to select tomographically unilateral cases with ≥3 years of follow‐up. For comparison, a healthy cohort and two bilateral KC cohorts were matched to the tomographically unilateral cases. All patients were selected from The Rotterdam Eye Hospital, whereas healthy controls were selected from the population‐based Rotterdam Study. After cohort selection, several risk factors and 25 Pentacam features were assessed. Unaffected (i.e. tomographically non‐keratoconic) eyes from the tomographically unilateral cases were compared to matched healthy eyes, matched bilateral KC eyes and affected unilateral KC eyes. Furthermore, affected tomographically unilateral KC eyes were compared to matched bilateral KC eyes. Statistical analysis relied on Wilcoxon signed‐rank tests and conditional logistic regression. Results From 1006 assessed cases, 18 (1.8%) tomographically unilateral cases were selected. Their median (interquartile range) follow‐up was 5.7 (4.3–8) years. Eczema and asthma were more prevalent among tomographically unilateral patients (28% each) compared to bilateral patients (6% and 9%) (p = 0.01 and p = 0.05, signed‐rank test). We could not detect meaningful Pentacam differences between unaffected unilateral eyes and matched healthy eyes. Expectedly, significant differences were detected between unaffected unilateral eyes and affected (bilateral or unilateral) eyes. Lastly, the ectatic features of affected unilateral eyes seemed comparable to their bilateral counterparts, but their high‐order aberrations were significantly lower. Conclusion Our findings support the existence of tomographically unilateral KC. Understanding how tomographic unilaterality ensues may offer valuable insights into KC aetiology.